Supermoms—Tired, admired, or inspired? Decoding the impact of supermom beliefs: A study on Indian employed mothers - Shalaka Sharad Shah; Smita Chaudhry; Shilpa Shinde (PLoS ONE, 2025)
Some days she is a supermom, some days just a mom, but most days a bit of both, and every day she strives to keep her oath! The study aims to unravel the perceptions and beliefs about ‘being a supermom’ and to explore its relationships with work-related factors. Our study aims to unravel the perceptions and beliefs of 306 Indian-employed mothers about ‘being a supermom’ and its relationship with work-related factors like self-efficacy, work engagement, and psychological well-being. Standardized scales were used for quantitative study and qualitative questions were used to understand the beliefs about the supermom notion. Frequency analysis for the perception of the supermom notion showed that 52% of mothers consider it detrimental to achieving success, while 48% consider it to be beneficial. A path analysis revealed that if the supermom notion is perceived as beneficial, it increases employed mothers’ self-efficacy; self-efficacy promotes work engagement, and work engagement increases psychological well-being. SEM confirmed that self-efficacy increases psychological well-being directly as well as through work engagement indicating partial mediation of work engagement. Findings suggest that while the supermom ideal can be exhausting and is often viewed as a myth or trap that negatively impacts psychological well-being, it can also serve as a source of inspiration and contribute positively to psychological well-being for some mothers.